Comment un diagnostic territorial partagé à partir du paysage peut-il contribuer à développer une intelligence commune du territoire ? - Christine Partoune (Projets de Paysage)
The article offers a reflexive analysis of a training process dedicated to a shared diagnosis of a territory based on the landscape, proposed by the Institut d’Eco-Pédagogie, a non-profit association situated in Liège specialised in environmental education and acknowledged in the field of continuous training. The frame of reference for the teachers is environmental education and education to the landscape, as well as the concept of a common intelligence of a territory. The training model resulting from this process comprises three key stages : an immersion phase for participants to relate to themselves, other participants and their living environment ; a phase for developing awareness of self in relation to the world ; and a phase for making an appraisal of the territory integrating a complex systemic approach of the living environment and a socio-cultural empowerment of the citizen. The strong and weak points of these methods are then discussed.